Literature review: the implementation of Sukuk structures - Abdul Saied, Galal Mohamed A.; Awang, Mohd Daud; Ahmad, Sa’odah (Universiti Islam Pahang Sultan Ahmad Shah, 2022)
This article seeks to review the implementation of Sukuk structures following Shariah-compliant and Maqasid Al Shariah principles. The analysis of this work employs a qualitative methodology based on the thesis, journals, papers, websites, and other sources to understand the implementation of the Sukuk structure. The findings of this research demonstrate that the application of Sukuk structures is the principal contribution instrument to the Islamic financial system in the money growth and preservation of hifth al-mal, one of the Maqasid Al Shariah pillars. Despite the considerable risks associated with investments in the Sukuk sectors (in comparison to conventional bonds), Sukuk markets nevertheless generate a substantial return in the financial market. In addition, the Sukuk legislation utilises international standards such as IFSB or AAIOFI structures, which play a crucial role in elucidating the rights of Sukuk issuers and holders and fostering transparency in Sukuk contracts and dispute settlement.